2017
DOI: 10.1039/c7np00002b
|View full text |Cite
|
Sign up to set email alerts
|

Contact chemosensation of phytochemicals by insect herbivores

Abstract: Contact chemosensation, or tasting, enables insect herbivores to identify nonvolatile metabolites in complex mixtures present in plants. The interplay of primary and secondary plant metabolites with gustatory receptors is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Many herbivorous insects have adapted to a limited range of host plants by overcoming plant defenses against insect herbivory, resulting in mono- and oligophagous insects (so-called specialist insects) [ 1 ]. In parallel, specialists are able to precisely distinguish their host plants from other nonhost plants in their ecosystem using chemical senses, including gustation and olfaction [ 2 ]. In general, gustation is important in determining the acceptance or rejection of a potential food source, whereas olfaction is required when searching for host plants from a distance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many herbivorous insects have adapted to a limited range of host plants by overcoming plant defenses against insect herbivory, resulting in mono- and oligophagous insects (so-called specialist insects) [ 1 ]. In parallel, specialists are able to precisely distinguish their host plants from other nonhost plants in their ecosystem using chemical senses, including gustation and olfaction [ 2 ]. In general, gustation is important in determining the acceptance or rejection of a potential food source, whereas olfaction is required when searching for host plants from a distance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feeding in insect herbivores is controlled by their physiological responses to phytochemicals that determine the acceptance or rejection of a leaf based on the balance of feeding stimulants and deterrents contained in plant leaves [ 3 , 11 , 12 ]. Chemical ecological studies have identified plant secondary metabolites as feeding stimulants and deterrents for many insect herbivores [ 2 ]. For example, with regard to the silkworm Bombyx mori , a specialist on mulberry leaves, Hamamura and his colleagues identified nonvolatile compounds from mulberry leaves as key signals: isoquercitrin (ISQ) and β-sitosterol (βsito) as biting factors and chlorogenic acid (CGA) as a feeding stimulant that increases feeding amounts in a long-term assay [ 11 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemosensory proteins (CSPs) are soluble and stable proteins consisting of 6 alphahelices stabilized by two disulphide bonds and a central channel with the capacity to bind small hydrophobic molecules, such as plant volatiles and insect pheromones (1,2). These proteins are often highly expressed in the olfactory and gustatory organs of insects in which they play a role in the sensing of the external environment by carrying volatiles and pheromones to neurons of chemosensilla, leading to downstream behavioural and developmental processes (3,4). For example, CSPs expressed in antenna regulate the transition from solitary to migratory phases of migratory locusts (5), female host-seeking behaviour of tsetse flies (6) and nest mate recognition of ants (2).…”
Section: Introductionmentioning
confidence: 99%
“…Herbivores establish preferences through different types of host-cues (9)(10)(11)(12). Chemical cues, including plant primary and secondary metabolites, are particularly important for herbivores, as they provide specific information about the identity, physiological status and nutritional value of host plants and tissues (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, sugars were found to mask the aversive taste of secondary metabolites (38). Despite these advances, we currently lack a detailed understanding of how primary and secondary metabolites interact to determine herbivore behavior under biologically realistic conditions (9). The paucity of manipulative experiments that test for interactions between host-derived chemical foraging cues in planta limits our capacity to assess the concerted impact of different metabolites on herbivore feeding preferences, and, more generally, our understanding of the role of plant metabolic complexity in herbivore behavior and plant-herbivore interactions.…”
Section: Introductionmentioning
confidence: 99%